PENGARUH ELEMEN KONTEKSTUAL TERHADAP INTENSI BERWIRAUSAHA MAHASISWA DIPLOMA III AKUNTANSI - Yanto Darmawan (Akademi Akuntansi YKPN Yogyakarta, 2018)
This study aims to investigate factors that influence entrepreneurial intention of student of Diploma III in accounting. The model which is analyzed include contextual factors (instrumen readiness, academic support and structural support). Data was obtained through questionnaires from 261 students of Akademi Akuntansi YKPN (AA YKPN) Yogyakarta. Data was analyzed by Structural Equation Modelling - Partial Least Square (PLS) using Smart PLS 2.0. The results of this research shows that the entrepreneurial intentions of students of Diploma III in accounting is influenced by instrumen readiness, and structural support. Keywords: entrepreneurial intention, subjective norm, contextual factors, partial least square